A convenient catalyst for aqueous and protein Suzuki-Miyaura cross-coupling. - Chalker, J; Wood, C; Davis, B (2009)
A phosphine-free palladium catalyst for aqueous Suzuki-Miyaura cross-coupling is presented. The catalyst is active enough to mediate hindered, ortho-substituted biaryl couplings but mild enough for use on peptides and proteins. The Suzuki-Miyaura couplings on protein substrates are the first to proceed in useful conversions. Notably, hydrophobic aryl and vinyl groups can be transferred to the protein surface without the aid of organic solvent since the aryl- and vinylboronic acids used in the coupling are water-soluble as borate salts. The convenience and activity of this catalyst prompts use in both general synthesis and bioconjugation.